Breast feeding and The Sustainable Development agenda - Katsinde, Shingirai Miranda; Srinivas, Sunitha Chandrasekhar (Indian Journal of Pharmacy Practice)
Breast feeding and exclusive breastfeeding practices are essential for infant and young child growth and development. The advantages of breastfeeding and exclusive breastfeeding contribute to the sustainable development as a core practice which not only affects children, but also adults and the world at large.
Keywords: breastfeeding; exclusive breastfeeding; sustainable development goals; global agenda; infant feeding